Personality Factor, Self Efficacy and Prevention of Cervical Cancer among Childbearing Age Women - Ni Ketut Alit Armini; Iqlima Dwi Kurnia; Fani Lailatul Hikmah (Jurnal Ners, 2016)
Introduction: Cervical cancer is a major cause of morbidity and mortality worldwide. Bad cervical cancer prevention program cause delays in treatment. Thus, leading most of the respondents had cervical cancer in advance stadium. The study aims to determine the correlation of personal factors, self efficacy in the prevention of cervical cancer in women of childbearing age. Methods: The study design was descriptive correlative with cross sectional approach. The population were all women of childbearing age in Puskesmas Kenjeran Surabaya. Samples were 64 respondents gathered by using simple random sampling. The independent variable were the personal factor and self efficacy. The dependent variable was the primary and secondary prevention efforts. Data were analyzed using Spearman's rho test to determine the variables which associated with the prevention of cervical cancer. Results: The results showed the correlation between personal factors and prevention of cervical cancer with p = 0.025 (α ≤ 0.05). While self efficacy had no correlation with the prevention of cervical cancer with p = 0.094 (α ≤ 0.05). Discussion: Personal factors related to the prevention of cervical cancer in women of childbearing age, while self efficacy is not related to the prevention of cervical cancer in women of childbearing age. For the next researcher to use other variables of the theory Health Promotion Model to take steps to prevent cervical cancer.